Development and characterization of singkamas (Pachyrhizus erosus) juice. - Valenzuela Jr., Jerry Macabanti
Singkamas (Pachyrhizus erosus) is a vegetable that grows annually in the Philippines and is reported to be a rich source of nutrients and minerals. This study utilized singkamas in juice making. The nutritional/physico-chemical properties of singkamas juice and pure concentrate were determined. The singkamas concentrate had a pH of 6.07 ± 0.19, TSS of 7.83% ± 0.50 % relative density of 1.047 g/mL ± 0.005 g/mL, crude fiber of 0.50% ± 0.06% (wet basis) and crude ash of 0.33% ± 0.17% (wet basis). Among the three formulations, the singkamas juice with 150mL of singkamas concentrate and with 500mL water was the most preferred by 12 panelists. The most preferred singkamas juice had a pH value of 4.64 ± 0.05, TSS of 5.94% ± 0.17 %, vitamin C content of 7.66mg ± 1.70mg per 100mL. The highest radical scavenging activity of the juice was at 400 ppm with 28.62% inhibition. Attribute testing showed that the singkamas juice was ?moderately sweet?, ?not sour?, had a ?strong singkamas aroma and flavor? and had a color of ?slightly pale cream?. Overall, the juice gained a general acceptability rating of ?like moderately? Singkamas juice formulated as 3:10 (or 150ml/500mL) concentrate-to-water ratio can be a functional drink containing minerals and vitamin C, with antioxidant activity that could inhibit radical formation.